LIPOSOMES: A NOVEL DRUG DELIVERY SYSTEM - Sharma, A; Rathor, P.; Bhandari, S. S.; Kabra, P. M. (Asian Journal of Pharmaceutical Research and Development, 2013)
In this review article we discuss about liposomes, these are one amongst the various drug delivery system used to target the drug to particular tissue .Because structure similarity between lipid bilayer and cell membrane, liposome can penetrate effectively deliver drug to such that a free drug would not penetrate. Liposomes have been widely investigated since1970 as drug carriers for improving the delivery of therapeutic agents to specific sites in the body. Liposomes, which are biodegradable and essentially non‐toxic vehicles, can encapsulate both hydrophilic and hydrophobic materials, and are utilized as drug carriers in drug deliverysystems. As a result, numerous improvements have been made, thus making this technology potentially useful for the treatment of certain diseases in the clinics. Liposomes have been considered as one of the most outstanding, versatile and flexible carrier systems, which offer wide opportunity for the delivery of multifarious molecules and applications. The present review focuses upon preparation, basic characteristic, marketed formulation and future prospectus and characterization of liposomes plus challenges associated with liposomal delivery. This review would be a help to the researchers working in the area of liposomal drug delivery.